Pendekatan Model Pengendalian untuk Mengurangi Risiko Akibat Gelombang Tsunami - Sriyana, Sriyana (Department of Civil Engineering, Diponegoro University, 2005)
Impact happened waving tsunami result very big loss of soul good and material and damage of nature and by psycology very harming for hit by society is accident. As does which have experienced of State of specially at Provinsi of Nangroe Darusalam, Sumatra North, Banyuwangi Ciity which have experienced of earthquake disaster and wave of tsunami. With existence of mentioned of hence needing the existence of effort which must be done to lessen risk of effect of earthquake disaster and wave of tsunami. Intention of this article is to give input of in the form of operation model alternatively to lessen risk of effect of wave of tsunami. Approach of operation model cover Early Information System warning, House Podium, Infill Escape Hill, Green Belt, Sea Wall or Dam, with approach of the model if executed hence risk faced will decrease. Keywords: approach of operation model, tsunamiPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3914[How to cite: Sriyana, 2005, Pendekatan Model Pengendalian untuk Mengurangi Risiko Akibat Gelombang Tsunami, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 106-113]